Analysis of the Readiness of Posyandu Cadres in Providing Basic Health Services Towards the Implementation of Primary Service Integration in Posyandu - Misrani Misrani; Sentot Imam Suprapto; Indasah Indasah (Indonesian Journal of Global Health Research, 2025)
The low achievement of health sector SPM in 2022 has driven the transformation of health services by optimizing the role of cadres in providing basic health services towards the integration of primary health care. Trials in various regions of Indonesia have shown positive results, but there is no clear picture of the readiness of cadres to implement integrated primary health care in Kotawaringin Barat. This study was conducted to explore the readiness of Posyandu cadres in providing basic health services in terms of appropriateness, change efficacy, management support, and personal benefit. This qualitative descriptive study was conducted in Posyandu located in the working area of Kumai Health Center, Kotawaringin Barat Regency, from September to November 2024. The research informants were 23 Posyandu cadres who met the criteria from the entire Kumai area. The main data was obtained from interviews, and additional data was obtained from cadre activity documents and observations of cadre performance in Posyandu implementation. Data analysis involves three main steps: data reduction, data presentation, and conclusion drawing. Data analysis successfully described findings from 5 themes and 20 sub-themes, including: cadre insight (sub-themes 1 and 2); appropriateness (sub-themes 3 to 5); change efficacy (sub-themes 6 to 12); management support (sub-themes 13 to 19); and personal benefit (sub-theme 20). Servant leadership needs to be developed to increase the internal motivation of cadres by optimizing the role of community leaders.